Leak in OpenSSL - Yapri, Jason; Hananto, Rinkel (Journal of Applied Information, Communication and Technology, 2020)
The term â€œhackerâ€ has been spread around the world and has always been considered as a threat when we use the internet. We often hear hackers deface websitesâ€™ contents and break into system to steal private and confidential information, such as accountâ€™s username and password, credit card numbers and others. This is definitely an unethical behavior of irresponsible people who mostly aims to gain profit. However the term hacker, on the contrary actually originates from an expert computer technicians who tries to access the system to debug and fix security problems of the system. Nowadays there are dozens of websites out there and some of those websites have low level of security. Hacker can easily break through their system and steal their private confidential data but just because these websites have low level security, that doesnâ€™t mean that it is ethical to break into someoneâ€™s system and read their data. It goes the same when someone entering other peopleâ€™s house because the door was left open by the owner. As web development grows rapidly, security has become an essential part to make the website more secure and reliable. This is when a group of people decided to make a collaborative project on the implementation of SSL (Secure Socket Layer) and TLS (Transport Layer Security) that is available to be used by everyone. This project is called as OpenSSl and has been used by most of the websites in the internet today. What if this OpenSSL, which has been trusted and implemented by 2/3rd of the websites all around the world can be breached? Definitely it will attract dozens of hackers all around the world to do something unimaginably dangerous.